Prevalence and associations for symptoms of depression in patients with Parkinson’s disease: a Sri Lankan experience - Herath, Tharaka B. (Int J Ment Health Syst, 2016)
BACKGROUND: The prevalence and associations for depression in patients with Parkinson’s disease vary widely between studies. This reflects the influence of cultural, demographic and socioeconomic confounders within communities that make generalizations invalid. Therefore it is important to identify unique attributes within a community on this phenomenon. This is the first study from Sri Lanka on the prevalence and associations for co-morbid depression in patients with Parkinson’s disease. METHODS: We conducted this cross sectional study at the Institute of Neurology, National Hospital of Sri Lanka. All patients with a diagnosis of idiopathic Parkinson’s disease followed up at the movement disorder clinic of the institute were enrolled. The patients were interviewed by investigators (medical practitioners) with an interviewer administered questionnaire that collected data on (a) demography, (b) clinical symptoms of Parkinson’s disease and (c) socioeconomic background. Symptoms of depression were assessed with Hamilton rating scale for depression. RESULTS: We enrolled 75 patients [males; 54 (75 %), mean age; 63.6 years, SD ± 6.8]. Forty-six (61.3 %) patients had been either formally diagnosed with depression or showed symptoms of depression. Bradykinesia, monthly income below Rs. 10,000 and having a family history of depression were significantly associated with a diagnosis of life-time post Parkinson’s disease depression (p < 0.05). CONCLUSION: Given the potential benefit in treatment (for depression), all patients with Parkinson’s disease should be screened for depression regularly. HAM-D would be a good screening tool for this purpose as it has good reliability, validity and can be administered within a reasonable time limit.